PENGARUH INSENTIF, MOTIVASI BERPRESTASI DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN PT. MAS SUMBIRI KENDAL - Fasochah -; fera lusvianawati (LPPM STIE DHARMAPUTRA SEMARANG, 2020)
ABSTRACTThe purpose of this study was to determine the effect of incentives, achievement motivation and career development on the performance of employees of PT. MAS Sumbiri Kendal. Samples were obtained by using random sampling technique which is a number of 80 samples that are employees of PT. MAS Sumbiri Kendal. The research data analysis tool uses multiple linear regression. Incentives have a positive effect on the performance of employees of PT. MAS Sumbiri is proven. This means that the higher the incentives, the higher the employee's performance. Achievement motivation has a positive effect on the performance of employees of PT. MAS Sumbiri is proven. This means that the higher the achievement motivation, the higher the employee's performance. Career development has a positive effect on the performance of employees of PT. MAS Sumbiri